HEALTH EDUCATION TO IMPROVE THE COMPLIANCE OF LOW SALT DIETS IN PATIENTS WITH HYPERTENSION - Beti Kristinawati; Riska Nurul Khasanah; Siti Rahmawati (Universitas Ahmad Dahlan, 2020)
Background: The level of knowledge of hypertensive people can influence obedience in running a low-salt diet. Low levels of public awareness about low-salt diets can be at risk of complications due to hypertension and death. Health education activities in this community aim to increase the understanding of patients with hypertension on the importance of low-salt diets to improve adherence to the exercise of the dietMethods: Educational methods used in the form of teaches and demonstrations in groups of people with hypertension in Drono village, Ngawen Sub-District, Klaten Regency.Results: Knowledge of the hypertension diet increased between before and after educational activities. Success demonstrated with increased knowledge scores before educational activities of 3.46 and after education score rose to 85.02.Conclusions: Devotion to the community in health education provides increased knowledge in the group of hypertension sufferers. This activity is expected to continue, programmatic, and developed with specialized training in cadres to improve the degree of public health.